The Translation Procedures on School Notices Board at SMAN 3 Kota Serang - Mulki Siti Rezaini (English Education Department, Postgraduate, Universitas Sultan Ageng Tirtayasa, Indonesia, 2019)
Translation has an important role especially for people in Indonesia. This is owing to the fact that only little information is available in Bahasa Indonesia. That is, a great deal of information is mostly presented in foreign languages, particularly in English. In this reseach, the writer discusses about translation in school notices school and researchers concent this reseach in one of senior high school in Serang. At this time in various schools the rules for the use of school bulletin boards that are affixed to the walls of the school and the language used in English with varying words have meaning. School notice board is a surface intended for the posting of public messages, for example, to advertise items wanted or for sale, announce events, or provide information. Researchers found that is the existence of writing errors in writing and translating words and also sentences on the school bulletin board because on the basis of a lot of bulletin boards in schools that use English language. In this study the researchers wants to analyze of translation procedures school notices board in senior high school.